Reasoning in the valuation of health‐related quality of life: A qualitative content analysis of deliberations in a pilot study - Fabia Gansen; Julian Klinger (Wiley, 2020)
Abstract Background Group deliberation can be a pathway to understanding reasons behind judgement decisions. This pilot study implemented a deliberative process to elicit public values about health‐related quality of life. In this study, participants deliberated scales and weights for a German adaption of the Short‐Form Six‐Dimension (SF‐6D) Version 2 from a public perspective. Objective This article examines the reasons participants stated for health state valuations and investigates the feasibility of eliciting public reasons for judgement decisions in a deliberative setting. Methods The 1‐day deliberation was guided by MACBETH as a method of multi‐criteria decision analysis and involved qualitative comparisons of SF‐6D health states and dimensions. Participants deliberated in parallel small groups and a subsequent plenary assembly. A qualitative content analysis was conducted to assess the value judgements and reasons behind them. Results A total of 34 students participated in the study. Common reasoning was the level of impairment, marginal benefit, possibility of adjustment and expectation satisfaction. While the small groups agreed on scales for the SF‐6D dimensions, the plenary assembly did not reach consensus on one scale and dimension weights. When dimensions were prioritized, these were pain and mental health. Conclusions While no consented value set was derived, this pilot study presents a promising approach for eliciting public reasoning behind judgements on health state values. Furthermore, it demonstrates that participants consider diverse motives when valuing health‐related quality of life.